TRAIL inhibits oxidative stress in human aortic endothelial cells exposed to pro‐inflammatory stimuli. Issue 20 (20th October 2020) - Forde, Hannah; Harper, Emma; Rochfort, Keith D.; Wallace, Robert G.; Davenport, Colin; Smith, Diarmuid; Cummins, Philip M.
Abstract: Studies suggest that tumor necrosis factor‐related apoptosis‐inducing ligand (TRAIL) has vasoprotective potential, as low levels of TRAIL cause accelerated vascular calcification, whereas exogenous TRAIL administration exhibits anti‐atherosclerotic activity. The mechanism of TRAIL‐mediated vasoprotection remains unclear. We studied the effects of TRAIL (100 ng/ml) on human aortic endothelial cells (HAECs) exposed to pro‐atherogenic conditions; (a) oscillatory shear stress (±10 dynes/cm 2 ) using the ibidi µ‐slide fluidic system; (b) pro‐inflammatory injury, that is, tumor necrosis factor alpha (TNF‐α, 100 ng/ml) and hyperglycemia (30 mM d ‐glucose). End‐points examined included inflammatory gene expression and reactive oxygen species (ROS) formation. TRAIL shifted the net gene expression toward an antioxidant phenotype in HAECs exposed to oscillatory shear stress. TRAIL significantly reduced ROS formation in HAECs exposed to both TNF‐α and hyperglycemia. Therefore, TRAIL appears to confer atheroprotective effects on the endothelium, at least in part, by reducing oxidative stress. Abstract : Human aortic endothelial cells (HAECs) were treated with recombinant TRAIL in the presence and absence of pro‐inflammatory stimuli (Tumour necrosis factor alpha and hyperglycaemia). TRAIL reduced reactive oxygen species formation in HAECs exposed to pro‐inflammatory, pro‐atherogenic conditions.